HUBUNGAN STATUS GIZI DENGAN USIA MENARCHE REMAJA PUTRI DI SMP GUNUNG JATI KEMBARAN KABUPATEN BANYUMAS - Linda Yanti; Nela Kristiana (Universitas Harapan Bangsa Purwokerto, 2012)
Background: nutritional factors that most influence on events menarche. As researchconducted Bielicky and Welon (1982) and Barsel (1978) in Folia Medica Indonesiana (2003)the amount of animal protein intake as an important factor causing the changes to the age ofmenarche among adolescent girls. Young women who eat meat every 13 hours on average toexperience menarche at age 11.64 years and young women who consume meat 1-4 times aweek on the average age of menarche be 13.46 years. Objective: To determine the nutritional status relationship with the age of menarche girls injunior Gunung Jati Kembaran Banyumas in 2012. Methods: This study is an analytic correlation, type of research approach is cross sectiona.The population in this study is a student in junior high Gunung Jati Twinning in the academicyear 2011/2012 which has experienced menarche is numbered 139 students and a sample istaken by the sampling technique used purposive sampling obtained 49 student. Results: The analysis showed no association between nutritional status and age of menarchegirls in junior Gunung Jati Kembaran Banyumas 2012. Ã¾-value> Î± (7.841> 3.981) so Horejected and Ha accepted. Conclusion. There was no association between nutritional status and age of menarche girls injunior Gunung Jati Kembaran Banyumas in 2012 Keywords: nutritional status, age of menarche, adolescent girls